Multidimensional Analysis of Overall Service Quality in Aesthetic Clinics as a Predictor of Recommendation Intentions - Norasiya, Milka Anisya; Antonio, Ferdi (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study investigates the impact of overall service quality on patient satisfaction and their intention to recommend aesthetic clinics, emphasizing the role of six quality dimensions measured as a higher-order construct (HOC). Understanding the influence of comprehensive service quality is crucial in aesthetic clinics, where patients seek more hedonic experiences rather than medical treatment. A survey was conducted among patients visiting aesthetic clinics, and Partial Least Squares - Structural Equation Modeling (PLS-SEM) with a disjoint two-stage approach was used to examine the relationships between the six reflective dimensions of service quality as lower order construct (LOC), namely technical, procedural, interactional, personnel, infrastructural, and social support with the outcomes of patient satisfaction and intention to recommend. The findings reveal the dimensionality of the service quality model in the aesthetic clinic context. In particular, overall service quality, measured as HOC, significantly influences patient satisfaction, which in turn positively affects the intention to recommend. Among the dimensions, technical quality and social support were critical in shaping patient perceptions and driving satisfaction. The model demonstrates robust explanatory and predictive power, with an R² value of 0.745 and Q²_predict of 0.679 for intention to recommend. A cross-validated predictive ability test confirms the model's predictive accuracy. Novel to this research is the comprehensive inclusion of quality dimensions, reflecting the complexity of service delivery in aesthetic clinics. The disjoint two-stage approach provides enhanced insights into the relative contributions of LOCs, highlighting technical quality, social support quality, and interactional quality as critical drivers of overall service quality. These findings offer actionable recommendations for managers to optimize service quality and encourage clinic recommendations.